An Assessment of the Current Chlamydia trachomatis Laboratory Practices in Germany - Schmidt, D.; Päschke, H.; Bremer, V.; Hamouda, O.; Reischl, U.; Sailer, A.; Haar, K. (Das Gesundheitswesen, 2014)
Currently, no information is available about the number of Chlamydia trachomatis (CT) tests performed, testing facilities available or diagnostic methods used in Germany. This study aimed to map CT diagnostic facilities so that representative laboratories can be recruited for CT sentinel surveillance.Using a questionnaire, we collected information about population coverage, the number of tests performed, accreditation and current testing methods and systems for German facilities that potentially offer CT diagnostics.Overall, 725/1 504 (48%) facilities responded; of the respondents, 143 reported that they perform CT diagnostics. Of the laboratories performing diagnostics, 45% were privately owned, and 42% were located in a hospital. Of the laboratories that provided information about their catchment area, 61% received samples from at least one federal state and therefore covered more than their surrounding area. The median length of time that CT diagnostics had been performed was 11.5 years. Over half (54%) of the laboratories that provided information on their accreditation status were accredited, for a median duration of 6 years. In accordance with national guidelines, 77% used nucleic acid amplification tests (NAAT) for acute CT infections.The long duration since Ct diagnostics have been performed and laboratories have been accredited can be seen as an indication of the high diagnostic quality of German laboratories. Additionally, laboratories mostly serviced doctors and patients from a large region and are not representative for people living in the area where the lab is located. This has to be considered when sampling representative labs for CT sentinel surveillance and further epidemiological studies.
Keywords: Chlamydia trachomatis (CT); sexually transmitted infection (STI); sentinel; Germany; nucleic acid amplification test (NAAT); laboratory